India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper uncovers the factors behind the unprecedented widening of India's current account deficit in terms of the sectoral savings-investment balance. The unprecedented widening of India's current account deficit in recent years is a symptom of underlying macroeconomic imbalances and structural weaknesses. Persistently high inflation has depressed real returns, prompting a surge in gold imports and a marked deterioration in household financial savings and the savings-investment balance. In turn, improvement in the public sector's savings-investment balance was achieved through capital spending cuts, as subsidies remained high and fuel price adjustments lagged. Further efforts to increase financial savings would help reduce the current account deficit sustainably and boost growth.